Indonesia's Global Maritime Fulcrum and Its Contribution in Maintaining ASEAN Maritime Security Stability - Purwanto, Adi Joko; Hidayah, Nikmatul (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2025)
This paper discusses Indonesia's maritime vision through Global Maritime Fulcrum during the administration of President Joko Widodo 2014-2019 and its contribution in maintaining ASEAN maritime security stability. Southeast Asia is a strategic region since the era of the second world war, the cold war and even today it is still a place of competition between the great powers of the world the United States and China. The competition between the United States and China at the global level has the potential to disrupt regional unity and make ASEAN fail to play its central role. The challenge provide an insight into the importance of Indonesia's role as the largest and most strategic country in Southeast Asia in maintaining the stability of regional maritime security. Indonesia's policy in the field of defense security will have an impact on ASEAN. The method used is a qualitative descriptive approach using secondary data such as review of academic articles, books, Journals, reports, and other relevant literature with two research questions First, what is the concept of Indonesia's maritime security in the Global Maritime Fulcrum policy? And Second, how does Global Maritime Fulcrum Policy contribute to maintaining the stability of ASEAN's maritime security? Keywords: Global Maritime Fulcrum, Maritime Security, ASEAN Maritime Security, Regional Stability